Prisoners of War in the Imperialist War - K. A. Grymzin (Сибирское юридическое обозрение, 2014)
The article is devoted to the law provision study of prisoners of war; here is considered the legal aspect of the issue, and the author quotes some facts and events which took place during the imperialist war.